Monetary policy rules in practice: Evidence from New Zealand - Angela Huang; Dimitri Margaritis; David Mayes (Bank of Finland, 2001)
We use the ten years of experience in inflation-targeting in New Zealand since 1989 to test whether monetary policy appears to conform to the simple rules that have been recommended for it in the literature.Of the inflation targeting central banks, the Reserve Bank of New Zealand has both the longest experience and probably the most clearly defined target and policy framework for achieving it.We show that while a Taylor rule with the standard parameters used in the US does indeed describe New Zealand monetary policy quite well, the Reserve Bank has focused rather more strongly on price stability, as required by its Policy Target Agreements.However, while the conduct of New Zealand monetary policy as set out in the Monetary Policy Statements is firmly based on targeting the inflation rate in the future we find, using the Bank's own forecasts, that nevertheless targeting inflation close to the present appears to be a better description of policy. Furthermore, restricting the policy choice to the information available to the Reserve Bank at the actual time of policy settings and ignoring subsequent revisions to published statistics does not result in a much improved explanation of its actions.We find a clear 'smoothing' element to the Bank's policy rather than immediate response to every small fluctuation.We show further that some of the variables that enter the policy rule have slightly asymmetric cycles.From symmetric and asymmetric cointegration tests on the long-run relationship between interest rates, the output gap, and inflation we show that there is insufficient evidence to suggest that monetary policy has been asymmetric in treating upside inflationary pressures differently from those towards deflation.
URN:NBN:fi:bof-20140807474
Keywords: 330; monetary policy; Taylor rule; inflation targeting; New Zealand